TRANSFER OF PANCASILA VALUES IN PROJECT BASED LEARNING (PLANNING, IMPLEMENTING, AND EVALUATING) FOR PGSD STUDENTS OF UMC (International Conference on Elementary Education, 2018)
Civics education in Indonesia more emphasis on moral aspects (individual character). The next generation through civics education is expected to anticipate a future that constantly changing and always related to the context of the dynamics of culture, nation, state, and international relations, as well as having love of the fatherland based on Pancasila. The purpose of this study was to determine the application of Pancasila values in Civics learning, and to find out the obstacles in project based learning in Civics learning for elementary school. This research use descriptive qualitative methods, with survey research design, and the instrument used a questionnaire. The focus of the research is planning, implementing and evaluating project-based learning based on transfer of Pancasila values in Civics learning to teacher students candidate, as well as obstacles that arise in the learning process. Respondents amounted to 30 people, they are students of SD16A2 class. The results of this study indicate that: 1) The planning is must be done carefully, considering the values of Pancasila consist of derivatives of 5 principles incorporated as Pancasila; 2) In the implementation, lecture must be able to direct students so the material associated with the 5 principles in Pancasila; 3) Evaluation of learning finds obstacles in the form of material delivery processes that are difficult for some students to understand, and difficult to make a red line from each of the Pancasila precepts. For this reason lecturers strive to provide examples contextually as an effort to deep material.